The origins of AIDS - Pepin, Jacques 1958- (Cambridge Univ. Press, 2012)
"This compelling new account traces the origins and development of the most dramatic and destructive disease epidemic of modern times. Jacques Pepin looks back to the early twentieth-century events in Africa that triggered the emergence of HIV/AIDS and the subsequent evolution and transmission of the disease before it was first officially identified in 1981. The book focuses on the specific circumstances in Leopoldville, the capital of the Belgian Congo, where urbanization, the spread of prostitution, and medical interventions to control the incidence of tropical diseases interconnected to fuel the communication of HIV-1 in the 1960s, as the country struggled to adapt to its newfound independence. With a unique synthesis of historical, political and medical elements, this book adds a coherent and necessary historical perspective to recent molecular studies of the chronology of the HIV/AIDS pandemic"--Provided by publisher